(untitled) (SCIÉNDO INGENIUM, 2021)
The purpose of this article was to establish how administrative management influences the contracting processes of the National University of Trujillo. Using a quantitative approach, cross-sectional and correlational design. The study was carried out with a sample of 73 servers from the user areas. The results show that, for 65.8% of the servers interviewed, the formulation of the university’s strategic plans is not adequate. On the other hand, 72.6% consider that the ability to delegate responsibilities according to the organization’s structure is not adequate. Also, for 91.8% of the servers in the user areas, the hiring processes are not efficient because the annual hiring plan is not fulfilled, nor the preparatory actions. Concluding that, administrative management significantly influences the contracting processes of the National University of Trujillo.